Depression, anxiety, stress, social interaction and health-related quality of life in men and women with unexplained chest pain - Manhem Karin; Lissner Lauren; Rosengren Annika; Kjellgren Karin I; Fagring Annika; Welin Catharina (BMC, 2008)
Abstract Background Unexplained chest pain (UCP) is a common reason for emergency hospital admission and generates considerable health-care costs for society. Even though prior research indicates that psychological problems and impaired quality of life are common among UCP patients, there is lack of knowledge comparing UCP patients with a reference group from the general population. The aim of this study was to analyse differences between men and women with UCP and a reference group in terms of psychosocial factors as depression, anxiety, stress, social interaction and health-related quality of life (HRQOL). Methods A self-administered questionnaire about psychosocial factors was completed by 127 men and 104 women with acute UCP admitted consecutively to the Emergency Department (ED) or as in-patients on a medical ward. A reference group from the general population, 490 men and 579 women, participants in the INTERGENE study and free of clinical heart disease, were selected. Results The UCP patients were more likely to be immigrants, have a sedentary lifestyle, report stress at work and have symptoms of depression and trait-anxiety compared with the reference group. After adjustment for differences in age, smoking, hypertension and diabetes, these factors were still significantly more common among patients with UCP. In a stepwise multivariate model with mutual adjustment for psychosocial factors, being an immigrant was associated with a more than twofold risk in both sexes. Stress at work was associated with an almost fourfold increase in risk among men, whereas there was no independent impact for women. In contrast, depression only emerged as an independent risk factor in women. Trait-anxiety and a low level of social interaction were not independently associated with risk in either men or women. Patients with UCP were two to five times more likely to have low scores for HRQOL. Conclusion Both men and women with UCP had higher depression scores than referents, but an independent association was only found in women. Among men, perceived stress at work emerged as the only psychosocial variable significantly associated with UCP.